Investigation of Various Parameters for Synthetic Zeolite Production From Turkish Fly Ashes - Akar, Gul; Ipekoglu, Oner; Emre Ertem, M.; Kanturk, Elif (Asian Journal of Chemistry, 2010)
Burning of coal in coal-fired electrical power generation plants produces solid waste in the form of boiler slag and fly ash. A large portion of this production is accounted for the coal fly ash. Coal combustion by-products in Turkey are about 45 million tons per year. This study focuses on the synthesis of zeolites from Soma and Yatagan power plant ashes in laboratory scale and on determining the conditions, which govern the related processes. In an alkaline ambient, fusion and hydrothermal treatment were applied as the test methods. The samples obtained from the experiments were investigated by electron microscope SEM and XRD. The final product was observed and determined to be sodalite, which has very similar crystal structure and properties as zeolite.